The State of Economy of Cotabato City during the Implementation of Martial Law Pursuant to Proclamation No. 216 - Datuali P Abdula; Lyn Marie Centeno; Tahir K. Salipada (RIRAI Publisher, 2022)
Mindanao was placed under Martial Law when President Rodrigo Duterte declared the suspension of the writ of habeas corpus on May 23, 2017 by virtue of Proclamation No 216. The call was made in an attempt to control the spread of threat brought about by the armed rebel Maute Group when they sieged Marawi City. Previous studies argued that a state is economically developed when the markets regulate themselves and the government has less intervention over it. It also concluded that dictatorship or strong political participation, when temporarily held, promote economic development. This study assessed the status of economy of Cotabato City as one of the areas of trade and commerce in Mindanao being affected by the implementation of Martial Law. Martial Law in the Philippines was always viewed as the military, headed by its Commander-in-Chief, the President, taking total control of the political power thereby inflicting negative impact on the state’s economy. The economic status of Cotabato City during Martial Law implementation was evaluated specifically in terms of trades, investments, local employment and tourism. Results presented that despite of Martial Law period, Cotabato City’s state of economy, particularly its activities on trades, investments, local employment and tourism, is high. This study showed that political intervention during the Martial Law implementation, does not affect the status of a city’s economy